Strategi Marketing Mix dalam Pemasaran Produk - Karuniawati, Chamila (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
The aim of this article is to describe marketing mix strategy in product marketing. Using literature review the discussion in this article yields the conclusion that:Â  the steps in implementing marketing mix strategies are: determining customer needs and desires, choosing special target market, pleacing marketing strategy in competiton, choosing marketing strategy. The are 4P marketing in the marketing mix strategy must be niticed: product, price, place, and promotion.Keywords: strategi, marketing mix, pemasaran produk.